Henry VIII, the Duke of Albany and the Anglo-Scottish War of 1522-1524. - Murphy, Neil (Boydell Press, 2023)
The first comprehensive study of this war helps us understand how each country to defend the frontier, and the political issues which drove the Anglo-Scottish wars of the 1520s.